KODIFIKASI RASM AL-QUR’AN (Sebuah Tinjauan Historis): KODIFIKASI RASM AL-QUR’AN (Sebuah Tinjauan Historis) - Abshor, M. Ulil (AR-ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2023)
The Qur'an couldn't be separated from the series of event and history of revelation bestowed on the Prophet. This matter is the reason for the difference in the writing of the Qur'an and the Hadis of the Prophet. The Qur'an at the era of the Prophet still had many sahabat who memorized the Qur'an, and at that time it had not been recorded and saved regularly in one Mushaf, still in the form of stone chip, date fronds and so on. but along with the events of the Yamamah war and many memorizers of the Koran died on the battlefield, the Messenger of Allah advised that there should be a delegation to collect the writing of the Qur'an into one mushaf. In writing the Koran led by Zaid Ibn Thabit, the method of collecting and writing the Qur'an was born. The writing of the Qur'an which we now know as Rasm al-Qur'an is called Rasm Uthmani. The Rasm Uthmani became an irreversible part of the Al-Qur'an Mushaf. Because of the accuracy of the verses of the Qur'an that have been agreed upon, the mutawatir history includes all verses that are not mansukh al-tiwalah. Then remove all writing that is not part of the verses of the Qur'an His writing include (al-Akhruf al-Sab'ah), as the Qur'an was revealed. The verses are as we can read in the verses that are arranged in the Qur'an today. The majority of scholars are of the opinion that Rasm Ottoman is tauqifi. Some scholars say that Rasm Ottoman is isthilahi, or the ijtihad of the companion.